Hemodynamic Disorders in Severe Brain Injury - Yu. A. Churlyaev; V. Ya. Martynenkov; L. Yu. Redkokasha; K. V. Lukashov; E. N. Denisov (Общая реаниматология, 2006)
This study was undertaken to determine the general regularities of hemodynamic disorders in relation to the severity of brain damage for the subsequent development of pathogenetically warranted methods for their correction in the complex of intensive care for severe brain injury. Studies were made in 67 victims, by using neurophysiological studies (electroencephalography, studies of acoustical stem-evoked potentials and somatosensory stem-evoked potentials), computed tomography and magnetic resonance imaging. Central hemodynamics was studied by a Sirecust 1260 monitoring system using Swan-Ganz catheters and thermodilution. The overall condition of the victims was regarded as very bad. Loss of consciousness was 8-4 scores by the Glasgow coma scale. The studies have indicated that the victims in whose clinical picture the signs of compression of the cerebral hemispheres dominate over those of the latter’s contusion develop a hemodynamic reaction by the normodynamic type. The hyperdynamic type of hemodynamic disorder develops in cerebral hemispheric and diencephalic lesions with a parallel increase in oxygen transport and uptake; and in severe brain injury, lower brain stem damages are accompanied by hemodynamic disorder by the hypodynamic type with a reduction in oxygen transport and uptake.